The Spectacle of Slogans: Media, Populism, and the Manufacturing of Consent in Pakistan: https://doi.org/10.55966/assaj.2025.4.1.059 - Dr. Amna Khurshid (`, 2025)
This study investigates the understanding between media, populism, and political slogans in Pakistan through the case of Pakistan Tehreek-e-Insaf (PTI). Drawing from Herman and Chomsky’s theory of “manufacturing consent” and Debord’s concept of the “spectacle,” the research explores how PTI slogans such as “Tabdeeli,” “Naya Pakistan,” and “Imported Hukumat Na-Manzoor” function as affective, visual, and rhetorical tools of political communication. Using a qualitative case study design, the study analyzes broadcast media, social media content, and party communications from 2013 to 2022. Through discourse and visual analysis, it demonstrates how slogans are used to simplify political narratives, construct emotional engagement, and foster political conformity. The findings reveal that PTI’s slogans transformed into cultural artifacts by leveraging mass media aesthetics, repetition, and leader-centric imagery. These slogans played a dual role: they mobilized supporters by offering emotional clarity and nationalistic pride, while simultaneously delegitimizing political opponents through binary framing. Media platforms, including television, Twitter, TikTok, and WhatsApp, amplified these slogans, saturating public consciousness and narrowing space for dissent or critical reflection. The study highlights the media’s complicity in reinforcing populist consensus, not through coercion, but via emotional spectacle and aesthetic saturation. Ultimately, the article argues that PTI’s slogan-driven populism exemplifies how media ecosystems in fragile democracies can become vehicles for symbolic control and manufactured political legitimacy. It underscores the urgent need for critical media literacy and further research into alternative political narratives in postcolonial societies. Keywords: Populism, Political Slogans, Pakistan Tehreek-E-Insaf, Media Spectacle, Emotional Mobilization, Manufacturing Consent, Political Communication, Discourse Analysis, Visual Politics, Populist Aesthetics